Pengaruh Persistensi Laba, Alokasi Pajak Antar Periode, Ukuran Perusahaan, Pertumbuhan Laba Dan Profitabilitas Terhadap Kualitas Laba (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI 2010-2012) - Sri Mala Afni; Vince Ratnawati; Yessi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to examine empirically the effect of earnings persistence, inter-period tax allocation, firm size, the growth of profit and profitability of the earnings quality. The population used in this study is manufacturing companies listed in indonesia stock exchange during the period 2010-2012, with a total population of 157 companies. This study used purpose sampling method, with a total sample of 36 companies. The method of analysis used in this study is the method of multiple linear regression analysis with spss version 17. Based on this research, it turns out the data normality test is not met, therefore the data transformation using the natural logarithm ( LN ) so that the data met the normality test. From the results of this study indicate that the earnings persistence and firm size significant negative effect on the earning quality. Inter- period tax allocation and the growth of profit significant positive effect on the earning quality . While profitability does not affect the earning quality. The magnitude of the effect that in this study was 21.3 % , while the remaining 78.7 % is influenced by other variables not examined in this study.Keywords: Earnings Persistence, Inter-Period Tax Allocation, Firm Size, The Growth of Profit, Profitability And Earnings Quality